Weyl algebra based key exchange protocol - Dvirnas, Albertas (Lietuvos matematikos rinkinys, 2014)
In this article we introduce the Weyl algebras as a platform algebra for a key exchange protocol based on the decomposition problem. In order to use it as a platform, we prove one propery of the Weyl algebra, related to it’s centralizer. Furthermore, we provide a scheme for the protocol and examples for the Weyl algebra and for the Weyl algebra with additional relations.